Fixel Based Analysis Reveals Atypical White Matter Micro- and Macrostructure in Adults With Autism Spectrum Disorder: An Investigation of the Role of Biological Sex - Kirkovski, Melissa; Fuelscher, Ian; Hyde, Christian; Donaldson, Peter H.; Ford, Talitha C.; Rossell, Susan L.; Fitzgerald, Paul B.; Enticott, Peter G. (Frontiers in Integrative Neuroscience, 2020)
Atypical white matter (WM) microstructure is commonly implicated in the neuropathophysiology of autism spectrum disorder (ASD). Fixel based analysis (FBA), at the cutting-edge of diffusion weighed imaging, is able to account for crossing WM fibers, and can provide indices of both WM micro- and macrostructure. We applied FBA to investigate WM structure between 25 (12 male, 13 female) adults with ASD and 24 (12 male, 12 female) matched controls. As the role of biological sex on the neuropathophysiology of ASD is of increasing interest, this was also explored. There were no significant differences in WM micro-or macro-structure between adults with ASD and matched healthy controls. When data were stratified by sex, females with ASD had reduced fiber density and cross-section (FDC), a combined metric comprised of micro- and macrostructural measures, compared to female controls, in the corpus callosum, a finding not detected between the male sub-groups. We conclude that micro- and macro-structural WM aberrations are present in ASD, and may be influenced by biological sex.